2018
DOI: 10.1007/s42452-018-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

β-ketoester-functionalized magnetoactive electrospun polymer fibers as Eu(III) adsorbents

Abstract: Blended polymer fibers based on a hydrophobic random copolymer having β-ketoester metal ion binding functionalities namely poly(methyl methacrylate)-random-poly(2-(acetoacetoxy) ethyl methacrylate) (PMMA-co-PAEMA) and the hydrophilic polyethylene oxide (PEO) were fabricated by electrospinning and further evaluated for the first time as adsorbents for the removal of Eu(III) from aqueous media. Moreover, magnetoactive fibrous analogues were prepared by incorporating preformed, oleic-acid coated Fe 3 O 4 NPs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
2
10
1
Order By: Relevance
“…The entropy increase upon uranium binding can be attributed to the release of water molecules, which lie around positively charged uranium and polar fiber surfaces, leading to an enormous increase in entropy upon adsorption. Compared to our previous study 50 where ΔH° and ΔS° were found to be 56.3 kJ mol −1 and 293.7 J K −1 mol −1 respectively, herein, the values of the thermodynamic parameters ΔH° and ΔS° are more favorable towards U(VI) adsorption, indicating that the presence of magnetic Fe 3 O 4 NPs has a positive effect on the adsorption process 49,77,78 …”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…The entropy increase upon uranium binding can be attributed to the release of water molecules, which lie around positively charged uranium and polar fiber surfaces, leading to an enormous increase in entropy upon adsorption. Compared to our previous study 50 where ΔH° and ΔS° were found to be 56.3 kJ mol −1 and 293.7 J K −1 mol −1 respectively, herein, the values of the thermodynamic parameters ΔH° and ΔS° are more favorable towards U(VI) adsorption, indicating that the presence of magnetic Fe 3 O 4 NPs has a positive effect on the adsorption process 49,77,78 …”
Section: Resultscontrasting
confidence: 73%
“…Finally, based on previous literature findings 49,55–57 it is expected that the anchoring of pre‐functionalized, double‐layer OA‐coated Fe 3 O 4 NPs will further enhance the adsorption capacity of the nanofibrous adsorbents.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In recent years, the fabrication, characterization, and applications of superparamagnetic polymer-based electrospun fibers has been made using highly stabilized superparamagnetic ferrofluids and polymers of various chemical compositions and functionalities (Figure 12). These include the preparation of white, superparamagnetic paper consisting of electrospun cellulose microfibers doped with iron oxide nanoparticles [195], superparamagnetic electrospun fibrous membranes consisting of β-ketoester-functionalized methacrylate-based polymers, and preformed, oleic acid-coated Fe 3 O 4 nanoparticles that were further evaluated as adsorbents for Eu(III) from aqueous media [196,197], surface-modified magnetic polyvinylpyrrolidone/chitosan blended electrospun nanofibers that were investigated as carriers in cell and enzyme immobilization [198], electrospun polymer-Fe 3 O 4 nanocomposite mats studied as dye adsorbents [199], and superparamagnetic electrospun nanocomposite fibers designed for use in the biomedical field [200,201]. Moreover, core-shell γ-Fe 2 O 3 /SiO 2 NPs, functionalized with fluorescent rhodamine B molecules, were combined with cellulose acetate electrospun fibers to yield multifunctional fluorescent fibrous nanocomposites employed as ammonia gas and pH sensors [202].…”
Section: Electrospinningmentioning
confidence: 99%
“…The electrospinning technique is simple, cost-effective, and industrially scalable [11,12], providing a straightforward way to produce long and continuous polymer fibers by using electrical forces. Moreover, electrospinning enables the incorporation of a variety of inorganic nanoparticles within or onto the fibers' surfaces [13], thus generating electrospun fibrous nanocomposites [14][15][16][17][18][19][20]. A distinct advantage of the fabrication methodology employed in the present study, making use of cellulose acetate electrospun fibers as host matrices for the anchoring of magnetic nanoparticles instead of conventional filter (cellulose) paper, is that the former are characterized by higher surface area and higher porosity due to their open pore structure, thus allowing the anchoring of increased amounts of MIONPs [21].…”
Section: Introductionmentioning
confidence: 99%